Optimization of PID Controller for a Hybrid Power System using Particle Swarm Optimization Technique - Bhumika Sahu; MPS Chawla; Sandeep Bhongade (Journal of Power Electronics and Devices, 2018)
With the advancement of technology, power demand is increasing day-by-day. Energy deficiency problem and increasing petroleum/diesel cost has resulted in severe impacts to many technical facts. Introduction of non- conventional energy sources such as wind and photovoltaic energy, which is clean and copiously present in nature, can be possible solutions to these problems. This paper presents optimization of a hybrid power system, with one of swarm intelligent algorithms named as particle swarm optimization (PSO).The hybrid system utilizes PID controllers for controlling its yield. It has been done by studying different combinations of diesel engine generator, wind turbine generator, aqua electrolyzer, fuel cell and battery. With the optimized system parameters, high quality power supply can be delivered to the load and the frequency fluctuations can also be minimized.